The Comparative Study of Transportation Mode Selection in Jakarta and Surabaya City - Hermanto Dwiatmoko (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2021)
The diversity of transportation modes that already exist today results in competition in the choice of modes, so that there are modes that are very much favored and used by travellers to achieve a destination. This study aims to observe the behavior of travelers who use public transportation buses with rail transportation in the city of Jakarta and the city of Surabaya in order to know the factors that influence travelers in making mode choices, in order to obtain a mode selection model that can explain the probability of travelers in choose the mode of urban transportation. For the city of Jakarta, research was conducted on the Hotel Indonesia – Blok M corridor, while in the city of Surabaya the research was conducted on transportation from Sidoarjo to Surabaya. The research was conducted by distributing questionnaires and direct observations in the field, then processed by the binary logit method to obtain multiple regression equations that describe the relationship between variables. The results of the study indicate that people are more likely to choose the bus mode of transportation with consideration of cheaper costs and faster arrivals to their destination. The results of this study can be used by local governments and transportation providers to improve urban transportation services in the city of Jakarta and the city of Surabaya.